Pengaruh Motivasi Kerja dan Budaya Organisasi terhadap Prestasi Kerja Karyawan PT Bank Mandiri Tbk Cabang Pematang Siantar Sudirman - Mas Intan Purba (LPPM STIE EKA PRASETYA, 2021)
The Effect of Work Motivation and Organizational Culture on Employee Job Performance of PT. Bank Mandiri Tbk Branch Pematang Siantar Sudirman. The purpose of this study was to determine and analyze the effect of work motivation and organizational culture on employee work performance at PT. Bank Mandiri Tbk. The method used in this study is a survey approach, the type of research is quantitative descriptive and the nature of this research is descriptive explanatory. The method of data collection is done by a list of questions and documentation study. The data analysis method used is multiple linear regression using SPSS software. The results showed simultaneously and partially work motivation and organizational culture had a positive and significant effect on employee work performance. The coefficient of determination (R square) of 0.918 which means that the ability of work motivation (X2) and Organizational Culture (X3) can explain variations of work performance by 91.8% and the remaining 8.2% is influenced by other variables outside of the variables studied.